2010
DOI: 10.1088/0031-9155/55/15/013
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional CT contrast agent for molecular imaging of cancer

Abstract: The purpose of this study was to investigate the feasibility of using a 2-deoxy-d-glucose (2-DG) labeled gold nanoparticle (AuNP-2-DG) as a functionally targeted computed tomography (CT) contrast agent to obtain high-resolution metabolic and anatomic information of tumor in a single CT scan. Gold nanoparticles (AuNPs) were fabricated and were conjugated with 1-DG or 2-DG. 1-DG provides an excellent comparison since it is known to interfere with the ability of the glucose transporter to recognize the sugar moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 36 publications
1
53
0
Order By: Relevance
“…Fayad and colleagues (174) reported the use of iodinated nanoparticles for cellular imaging of macrophage infiltration in atherosclerotic plaques in rabbits using MDCT. Also, a number of research groups have recently reported the use of targeted gold nanoparticles (known to induce strong X-ray attenuation) with CT for imaging cancer at the cellular and molecular levels (244,340). For example, one group reported the synthesis and evaluation of CT-compatible gold nanoparticles functionalized with prostate specific membrane antigen (PSMA) RNA aptamers (210).…”
Section: Ctmentioning
confidence: 99%
“…Fayad and colleagues (174) reported the use of iodinated nanoparticles for cellular imaging of macrophage infiltration in atherosclerotic plaques in rabbits using MDCT. Also, a number of research groups have recently reported the use of targeted gold nanoparticles (known to induce strong X-ray attenuation) with CT for imaging cancer at the cellular and molecular levels (244,340). For example, one group reported the synthesis and evaluation of CT-compatible gold nanoparticles functionalized with prostate specific membrane antigen (PSMA) RNA aptamers (210).…”
Section: Ctmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] Similarly, imaging contrast agents result in flux suppression and beam hardening but the changes are gradual and no sharp interface effects are observed. New contrast agents are continually under development [43][44][45] and are of potential use not only in imaging but also in radiotherapy. CERT has been studied by various authors mostly from MC computational and treatment planning standpoints.…”
Section: Macroscopic Dose Enhancement and Dose At High-z Interfacesmentioning
confidence: 99%
“…Multiple imaging modalities have been developed for in vivo molecular imaging, each on different field-of-view and resolution scales, and each with their own advantages and disadvantages. Whole body imaging techniques include magnetic resonance imaging (MRI) [3], computed tomography (CT) [4] and positron emission tomography (PET). These whole body imaging techniques have no limit on imaging depth, but are usually high cost methods, with poor sensitivity to the molecular contrast agent (CT, MRI) and/or involve the use of ionizing radiation (CT, PET).…”
Section: Introductionmentioning
confidence: 99%